N-terminal acetylation: an essential protein modification emerges as an important regulator of stress responses - Linster, Eric; Wirtz, Markus (The journal of experimental botany, 2018)
In this review, we summarize the current knowledge on the NAT machinery in higher plants and discuss the potential function of NTA during biotic and abiotic str